PERLINDUNGAN HUKUM BAGI GURU YANG MANGALAMI PENGADUAN AKIBAT TINDAKAN GURU SAAT MENJALANKAN PROFESI MENGAJAR - Nanang; Herlina Manullang; July Esther (Magister Hukum Universitas HKBP Nommensen, 2022)
Legal protection for teachers is interpreted as efforts made by the government to protect teachers and other education personnel in carrying out their professional duties, both protection in legal, welfare, professional and social aspects. Through research conducted in a normative juridical manner, this study concludes that legal protection for teachers in the education process related to violent crimes has been fully regulated in various laws such as Law Number 14 of 2005 concerning Teachers and Lecturers and Government Regulation Number 74 of 2008 About Teachers. Where it is explained in the two laws that punishment and sanctions are given to students with the aim of teaching by the teacher not to be a violent crime. Legal protection for teachers in the educational process related to acts of violence in the education sector should be implemented using a penal policy and a non-penal policy. The use of this policy by looking at the factors and background of criminal acts in the field of education occurred, especially by considering the objectives of the teaching process carried out by teachers.